2011
DOI: 10.1007/s11655-011-0755-6
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the standardization of Chinese Tuina therapy: A short review

Abstract: The standardization of Chinese Tuina therapy is one of the most popular research topics in Chinese medicine. By reviewing the literatures contributed by Chinese investigators between 1982 and 2010, the authors summarized the progress on Chinese Tuina manipulation techniques, in particular, focusing on the data on several key parameters (i.e., frequency, duration, and force). This summarization will benefit the standardization of Chinese Tuina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…And no dose-response study design was found in all the literatures. In the third place, our review clearly described massage techniques as stand-alone treatments without cervical manipulation or mobilization techniques, but there is the lack of consistent terminology for massage therapy, as reported by others [51, 52]. Fourthly, the included scales were mainly used to evaluate the variation of pain, whereas other scales in relation to cervical spine function or quality of life were not enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…And no dose-response study design was found in all the literatures. In the third place, our review clearly described massage techniques as stand-alone treatments without cervical manipulation or mobilization techniques, but there is the lack of consistent terminology for massage therapy, as reported by others [51, 52]. Fourthly, the included scales were mainly used to evaluate the variation of pain, whereas other scales in relation to cervical spine function or quality of life were not enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Tuina massage encompasses techniques as grasping, pressing, rolling, round rubbing, holding-twisting, rub rolling, pushing, kneading, rotating, shaking, wiping, vibrating, digital striking, knocking, chapping, pressing, acupressure, myofascial release, reflexology, stretching techniques and joint mobilizations applied to specific body points [ 76 ]. Tuina is a functional massage and it can input substantial proprioceptive sensory impulses to the central nervous system through muscle, tendon and joint motion [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over thousands of years, the scope of Tuina progressively increased not only in Chinese civilization but also in other cultures, and evidently this trend dynamically ongoing and enduring. At present, Tuina is used around the world and has many forms, techniques, procedures, and several underlying mechanisms of action [1,5,[8][9][10]. In addition, Tuina is based on certain theories and principles [5, [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 110 diverse manipulations, though only 20-30 are commonly used [8]. Although some progress is made concerning standardization of Tuina technique (i.e., frequency, duration and force) [9], further advances are required to match the evolving newer techniques of Tuina massage around the world.…”
Section: Tui Na Techniquementioning
confidence: 99%